2023
DOI: 10.3389/fcimb.2023.1136217
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and circulation of azole-resistant C. albicans, C. auris and C. parapsilosis bloodstream isolates carrying Y132F, K143R or T220L Erg11p substitutions in Colombia

Abstract: MethodsOver a four-year period, 123 Candida bloodstream isolates were collected at a quaternary care hospital. The isolates were identified by MALDI-TOF MS and their fluconazole (FLC) susceptibility patterns were assessed according to CLSI guidelines. Subsequently, sequencing of ERG11, TAC1 or MRR1, and efflux pump activity were performed for resistant isolates.ResultsOut of 123 clinical strains,C. albicans accounted for 37.4%, followed by C. tropicalis 26.8%, C. parapsilosis 19.5%, C. auris 8.1%, C. glabrata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…An epidemiologic study conducted between 2008 and 2010 on candidemia in Latin America found that in Colombia, C. parapsilosis (38.5%) and C. albicans (36.7%) predominated, followed by C. tropicalis (17.4%), C. glabrata (4.6%) and C. guilliermondii (1.8%) [1]. However, in the last years, the situation has changed with the emergence of C. auris throughout the country [20,29]. Despite cases of infections by C. auris being described in several cities, most of the cases have been concentrated on the Atlantic coast [16,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An epidemiologic study conducted between 2008 and 2010 on candidemia in Latin America found that in Colombia, C. parapsilosis (38.5%) and C. albicans (36.7%) predominated, followed by C. tropicalis (17.4%), C. glabrata (4.6%) and C. guilliermondii (1.8%) [1]. However, in the last years, the situation has changed with the emergence of C. auris throughout the country [20,29]. Despite cases of infections by C. auris being described in several cities, most of the cases have been concentrated on the Atlantic coast [16,29].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the drug-target lanosterol 14-α-demethylase ERG11 gene such as Y132F, K143R and F126L frequently lead to azole resistance in C. auris strains. Additionally, mutations in the transcription factor TAC1 can cause an overexpression of CDR1, which also leads to high-level azole resistance in C. auris [20].…”
Section: Introductionmentioning
confidence: 99%
“…6 We confirm that fluconazole resistance in C. parapsilosis is dominated by the presence of the Y132F substitution reported. 7,14,16,[30][31][32][33] Most of our isolates harboured Y132F ± R398I ERG11p substitutions, were included in clonally related genotypes, and were unrelated to genotypes harbouring only the Y132F substitution. Genotypes involving non-Y132F substitution isolates were unrelated and did not seem to associate with vigorous hospital transmission.…”
Section: Isolates Harbouring Non-y132f-g458s Erg11p Substitutionsmentioning
confidence: 92%
“…The common usage of azoles has contributed to azole-resistance among Candida spp., which complicates the treatment of patients suffering from candidiasis [9,10]. Therefore, searching for natural compounds that are active against fungal pathogens or that improve the activity of commonly used azoles remains a key research aim of modern medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Since azoles influence the structure and functioning of the fungal PM, we considered how a combination of PSZ and SU or CA would impact the growth of C. albicans mutants with alterations in ergosterol (C. albicans KS058 strain, lacking ergosterol in the PM due to the full deletion of ERG11, and three C. albicans strains, 10C1B1I1, 27A5A33A and 9B4B34A, with amino-acid substitutions in Erg11p) or mutations impacting the sphingolipids (SLs) biosynthesis pathway (C. albicans strains lacking FEN1, FEN12 or both genes). We also investigated whether perturbations The common usage of azoles has contributed to azole-resistance among Candida spp., which complicates the treatment of patients suffering from candidiasis [9,10]. Therefore, searching for natural compounds that are active against fungal pathogens or that improve the activity of commonly used azoles remains a key research aim of modern medicine.…”
Section: Introductionmentioning
confidence: 99%